2021
DOI: 10.1101/2021.02.18.431835
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rotavirus as an Expression Platform of the SARS-CoV-2 Spike Protein

Abstract: Rotavirus, a segmented double-stranded RNA virus, is a major cause of acute gastroenteritis in young children. The introduction of live oral rotavirus vaccines has reduced the incidence of rotavirus disease in many countries. To explore the possibility of establishing a combined rotavirus-SARS-CoV-2 vaccine, we generated recombinant (r)SA11 rotaviruses with modified segment 7 RNAs that contained coding sequences for NSP3 and FLAG-tagged portions of the SARS-CoV-2 spike (S) protein. A 2A translational element w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
(64 reference statements)
1
2
0
Order By: Relevance
“…With the exception of T2A_RBM, NSP3 mutants expressing SARS-CoV-2 spike peptides cross-reacted with the SARS-CoV-2 RBD antibody (Fig. 6B), supporting the previously proposed viability of using NSP3 as a tagging system [52] and demonstrating its application to other RV strains. Follow up studies using sera from COVID-19 patients are needed to confirm antibody responses to the antigens produced by the NSP3 mutants.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…With the exception of T2A_RBM, NSP3 mutants expressing SARS-CoV-2 spike peptides cross-reacted with the SARS-CoV-2 RBD antibody (Fig. 6B), supporting the previously proposed viability of using NSP3 as a tagging system [52] and demonstrating its application to other RV strains. Follow up studies using sera from COVID-19 patients are needed to confirm antibody responses to the antigens produced by the NSP3 mutants.…”
Section: Discussionsupporting
confidence: 76%
“…Previous studies have shown that SA11 NSP3 is able to tolerate insertions of foreign sequences at its C-terminus [45, 51, 52]; we have demonstrated that this is also possible using the bovine RF strain NSP3. This is advantageous as the current live attenuated pentavalent RV vaccine, RotaTeq, utilises a bovine RV backbone reassorted with different human strains and the use of a non-primate origin RV vector helps to circumvent pre-existing immunity [10, 69, 95].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation